Qualitative dissertation methodology a guide for research design and methods - Durdella, Nathan (Los Angeles SAGE, 2019)
"Qualitative Dissertation Methodology: A Guide for Research Design and Methods functions as a dissertation advisor to help students construct and write a qualitative methodological framework for their research. Drawing from the challenges author Nathan Durdella has experienced while supervising students, the book breaks down producing the dissertation chapter into smaller pieces and goes through each portion of the methodology process step by step. With a warm and supportive tone, he walks students through the process from the very start, from choosing chairs and developing qualitative support networks to outlining the qualitative chapter and delving into the writing. By the end of the book, students will have completed the most challenging chapter of a qualitative dissertation and laid a strong foundation for the rest of their dissertation work."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dissertations, Academic -- Methodology; Qualitative research -- Methodology